The Essence of Islamic Philosophy - Erna Robiatul Adawia; Maspuroh; Ahmad Daud; Muhammad Nursyauqi (Penerbit Hellow Pustaka, 2025)
Islamic philosophy is a form of thought that emerged within the intellectual tradition of the Islamic world, aiming to understand and explain the reality, existence, and essence of God using both reason and revelation. This article aims to examine the essence of Islamic philosophy by considering five main aspects: articulation, objectivity, method, utility, and its relationship with Greek philosophy. In terms of articulation, Islamic philosophy seeks to connect rational thought with divine revelation, resulting in a comprehensive worldview. From the perspective of objectivity, Islamic philosophy strives to uncover the absolute truth originating from Allah SWT through rational and revelatory approaches. The method used in Islamic philosophy involves logical and systematic thinking based on the teachings of the Qur'an and Hadith, as well as the works of great philosophers such as Al-Farabi, Ibn Sina, and Al-Ghazali. The utility of Islamic philosophy is evident in its application as a guide to understanding life, morality, and the higher purposes of existence. Lastly, the relationship between Islamic philosophy and Greek philosophy reflects the process of integrating classical Greek thought with Islamic thought, enriching the development of science and rational thinking. Therefore, Islamic philosophy not only contributes to scientific knowledge but also enriches the spiritual and moral dimensions of humanity.